Occurrence of Tetrodotoxin in Marine and Brackish Puffer Fish from East Malaysian Waters - Mohd Din, Monaliza; Samsur, Mohamad (2010)
Tetrodotoxin (TTX) is the toxic principle of puffer fish poisoning, a powerful and specific sodium channel blocker. TTX is exogenous in origin and accumulates in puffer fish through the food chain. Attempts were made to assess the toxicity, and verify toxin properties of marine and brackish puffers Lagocephalus lunaris, Tetraodon nigroviridis and Xenopterus naritus. The presence of TTX in puffer fish tissues were examined and verified by using mouse bioassay, Thin Layer Chromatography (TLC) and Gas Chromatography Mass Spectrometry (GC-MS). Toxicity assessment by mouse bioassay revealed that L. lunaris and T. nigroviridis was toxic (2.5 – 3.8 MU/g and 30.0 – 31.2 MU/g respectively). Meanwhile, thetoxicity scores of toxin extracted from tissues of X. naritus were 2.0 – 2.8 MU/g and the toxin were considered too mild to be detected since the mice did not die within 30 minutes after intra-peritoneally injection. Analysis of TLC showed that tissue extracts of L. lunaris, T. nigroviridis and X. naritus were positive for TTX. From the GC-MS analysis, it was unambiguously concluded that L. lunaris, T. nigroviridis and X. naritus exhibited TTX in their skin and muscle.